Wind turbine aerodynamics modeling by meshless method. Issue 3 (June 2021) - Mnebhi-Loudyi, Asmae; Boudi, El Mostapha; Ouazar, Driss
This article presents wind turbine aerodynamics modeling by a meshless method. This method does not require meshing but it requires only a set of nodes. The radial basis function of finite difference method is a local meshless method, which is the coupling between the radial basis functions and the finite difference methods. When the number of nodes increases, the system might become ill-conditioned. Therefore, the local meshless method is adopted. It must be noted that Navier–Stokes equation is the one used for modeling purposes. Numerical results were compared to the meshless method and the finite element method results in terms of both velocity and pressure. Close agreements are observed.